The Simultaneous Influence of AI Literacy and Prompting Skills on Students' Critical Thinking Disposition - Fitri Azzahra Hanifatunnisa; Jaka Septiadi (FKIP - Universitas Riau, 2026)
This study examines the influence of AI Literacy and Prompting Skills on university students’ Critical Thinking Disposition in the context of Generative AI use in higher education. A quantitative cross-sectional survey design was employed. The population consisted of 354 students from the Educational System and Information Technology Study Program at Universitas Pendidikan Indonesia, with 188 respondents selected using Slovin’s formula and purposive sampling. Data were collected through a closed-ended questionnaire using a five-point Likert scale to measure AI Literacy, Prompting Skills, and Critical Thinking Disposition. Data were analyzed using descriptive statistics and multiple linear regression after all classical assumptions were met. The results show that all variables are categorized at a high level. Partially, AI Literacy and Prompting Skills each have a positive and significant effect on Critical Thinking Disposition. Simultaneously, both variables explain 46.4 percent of the variance in students’ Critical Thinking Disposition. These findings indicate that students’ critical thinking disposition in the era of Generative AI is influenced by both conceptual understanding and technical competence in interacting with AI. Therefore, strengthening AI literacy and prompting skills should be integrated into higher education learning development strategies.